Effect of HPV integration on prognosis of young women with CIN2 in China: protocol for a multicentre prospective cohort study - Yan Zhang; Huachun Zou; Wei Zhang; Xiaoyuan Huang; Yuan Ren; Ting Hu; Wenyu Lin; Pengming Sun; Kelvin Stefan Osafo; Binhua Dong; Yuhang Zhang; Xiaowen Pu; et al. (BMJ Open)
Introduction Cervical cancer, a major global health concern, is primarily caused by human papillomavirus (HPV) infection. Although cervical intraepithelial neoplasia grade 2 (CIN2), a precancerous lesion, exhibits high spontaneous regression rates (50%–60%), particularly in younger women, current clinical management lacks accurate risk stratification. This study examines HPV integration status as a prognostic biomarker in women aged 18–45 diagnosed with CIN2, with the objective of developing a predictive tool for personalised therapeutic strategies and minimising overtreatment in this high-regression population.Method and analysis This multicentre cohort study will be implemented across 20 tertiary Grade A hospitals in China, encompassing eastern, western, central and northern regions. It will recruit 240 CIN2 patients, collecting sociodemographic, lifestyle and medical history data via questionnaires. Clinical examinations will be performed at baseline and follow-up. Disease regression ((to cervical intraepithelial neoplasia grade 1 [CIN1] or lower)) and non-regression (persistent CIN2 or progression) will be evaluated. Prognostic factors will be analysed using Cox proportional hazards models, adjusting for confounders such as age, weight and socioeconomic status.Ethics and dissemination The cohort study protocol and informed consent procedures adhere to the Declaration of Helsinki and pertinent Chinese clinical research regulations. Ethical approval has been obtained from the Clinical Research Review Committee of the Fujian Maternal and Child Health Hospital (2022KYLLR01018) and from the participating hospitals. Written informed consent is secured from all participants prior to enrolment, with detailed information provided regarding study objectives, procedures, potential risks and benefits and participants’ rights. Results will be published in peer-reviewed scientific journals, presented at academic meetings and conferences and released to the public through press releases.Trial registration number ClinicalTrials.gov (NCT05282095); Pre-results.